Hubungan Antara Kecerdasan Visual-Spasial Dengan Kemampuan Kognitif Anak Usia Dini - Nasution, Fauziah; Hasibuan, Afrah Nadhilah; Pitriana, Eka Riski; Lubis, Khoiriyah Anggina Br; Siregar, Riska Anita; Hasibuan, Yuli Anisah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Visual-spatial intelligence is one of the important aspects of early childhood cognitive development that involves the ability to perceive, process, and think in visual as well as spatial forms. Children with good visual-spatial intelligence are capable of accurately recognizing shapes, colors, spaces, and patterns, as well as having high imagination and creativity. This study aims to examine the relationship between visual-spatial intelligence and early childhood cognitive abilities, particularly in terms of problem solving, understanding of spatial concepts, and creativity. Study results show that visual-spatial intelligence plays a significant role in supporting children’s cognitive abilities, including in the learning process and understanding of visual and abstract material. The development of this intelligence can be done through a variety of activities such as drawing, playing puzzles, and exploring the environment that stimulate the child’s visual imagination. Thus, strengthening visual-spatial intelligence can improve a child’s overall cognitive ability.